Marxism and scientific socialism : from Engels to Althusser - Thomas, Paul (Routledge, 2008)
Engels declared at Marx’s funeral in Highgate Cemetery that "just as Darwin discovered the law of development of organic nature, so Marx discovered the law of development of human history". Scientific socialism was the term Engels used to describe Marx's socio-economic philosophy and many later theorists sought to reinforce Marxist theory with a supposedly scientific basis.